Meta-Analysis the Effectiveness of Fluoride Varnish Use to Prevent Deciduous Dental Caries in Children - Asrori Ibnu Utomo; Bhisma Murti; Eti Poncorini Pamungkasari (Journal of Epidemiology and Public Health, 2023)
Background: Oral health has improved in the last century but the prevalence of dental caries in children remains a significant clinical problem. Giving fluoride varnish directly to the surface of a child's teeth can prevent caries. This study aims to analyze the effect of using fluoride varnish on the prevention of dental caries in children.Subjects and Method: This research is a systematic review and meta-analysis research by considering the eligibility criteria using the PICO model. Population: children. Intervention: fluoride varnish. Comparison: do not use fluoride varnish. Outcome: DMF-T. Articles in this study were searched through the PubMed, Google Scholar, Science Direct, ProQuest databases with the keywords “effectiveness” AND “fluoride” AND “dental caries” AND “prevention” AND (“child OR children”) AND “randomized controlled trial”. The inclusion criteria in this study were full-text articles from 2000 to 2022 with randomized controlled trials (RCT) designs and mean SD effect sizes. This study uses PRISMA flow diagrams and uses the Revman 5.3 application for analysis.Results: A meta-analysis of 5 articles showed that the use of fluoride varnish reduced DMFT 1.21 units lower, compared to those not using fluoride varnish in children. The results of the meta-analysis were statistically significant (SMD = -1.21; 95% CI = -3.15 to 0.74; p= 0.220).Conclusion: The use of fluoride varnish may decrease DMFT in children. Keywords: dental caries, Fluoride varnish Correspondence: Asrori Ibnu Utomo, Masters’ Program in Public Health, Universitas Sebelas Maret. Jln. Ir. Sutami 36A, Surakarta 57126, Jawa Tengah, Indonesia. Email: asrori.ibnu69@gmail.com. Mobile: +62895359099137.